A Preliminary Evaluation of Mould Prediction Models Based on Laboratory Experiments. (November 2015) - Vereecken, Evy; Vanoirbeek, Kristof; Roels, Staf
Abstract: This paper presents a preliminary study on the validity of the mould prediction models frequently applied in the building physics field (VTT model, Sedlbauer's isopleths, biohygrothermal model), and this based on laboratory results found in the literature. Although similar laboratory experiments serve as the input for the development of the prediction models, quite large discrepancies are observed. These findings can be used when, for instance, upgrading the current mould prediction models. Apart from a correct conversion of measurements into the mould prediction models, the collection of reliable data sets is of course of seminal importance. Therefore, additionally, some potential difficulties, challenges, etc. in experimental mould growth research will be put forward.